PERSEPSI MAHASISWA FAKULTAS HUKUM UNIVERSITAS MULAWARMAN TERHADAP PROGRAM ACARA TALKSHOW “HOTMAN PARIS SHOW” DI INEWS TV - Abdul Rahman; Nurliah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
I-News TV has started to include entertainment and talkshows in its programs, one of which is the Hotman Paris Show. The Hotman Paris Show program continues to be broadcast on television in several episodes which are controversial or prohibited. The impact of the figure of Hotman Paris is reflected in the motivation that creates perceptions among Law Faculty students. One of the things that went viral was the perception of new students at the University of North Sumatra, Medan, because they saw the Hotman Paris Show program as one of the reasons for entering the Faculty of Law. This study aims to find out the perceptions of students of the Faculty of Law, University of Mulawarman towards the "Hotman Paris Show" talk show program on iNews TV. The phenomenon of I-News TV which incorporates entertainment and talkshows into its program range, one of which is Hotman Paris Show I-News Tv, which originally presented news and sports programs. The research method used is descriptive qualitative method of gathering information through observation, interviews, documentation and internet searching/document research. Sources of information using purposive sampling are informants who are directly related to research, namely students of the Faculty of Law, University of Mulawarman who have participated in public speaking. The results of the study show that perceptions of the "Hotman Paris Show" Talk Show Program on iNews TV are quite diverse, the selection perception that the Hotman Paris Show program has appeal because the hosts are lawyers. the perception of the organization where the informant felt that the "Hotman Paris Show" program was considered to be lacking in discussing and studying legal issues. Perception of interpretation where informants can judge that the "Hotman Paris Show" Talk Show Program still needs to be reviewed for the concept of the program which is addressed to whom the program is targeted at. The results of the study are in accordance with Lasswell's definition that communication delivered to the communicant from the communicator through certain channels either directly/indirectly aims to have an impact/effect on the communicant according to what the communicator wants. The indicators of student perceptions in this study are perceptions of selection, perceptions of organization and perceptions of interpretation.